2017
DOI: 10.1177/2324709617690746
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Plasmacytic Proliferation in a Case of C3 Glomerulopathy

Abstract: An 11-year-old Hispanic female underwent evaluation of asymptomatic proteinuria and hematuria. The patient denied fever, edema, and gross hematuria. Urinalysis showed mild proteinuria, and a urine microscopic examination revealed red blood cells. Screening tests for glomerulonephritis revealed a low C3 and negative ANA, ASO, DNAse-B, and ANCA. Histological examination of a renal biopsy specimen showed glomeruli with endocapillary proliferation, a predominant C3 deposition in the capillary loops by immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 18 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…C3Nef frequently coexists with anti-CFH, possibly having a synergistic effect on AP dysregulation in plasma. In a single report, anti-CFH was also associated with monoclonal Ig (35% cases in the small group of 17 patients), which is in line with previous reports of monoclonal Ig pathogenic involvement in C3G [82,83,99].…”
Section: Acquired Ap Abnormalities In C3gsupporting
confidence: 89%
See 4 more Smart Citations
“…C3Nef frequently coexists with anti-CFH, possibly having a synergistic effect on AP dysregulation in plasma. In a single report, anti-CFH was also associated with monoclonal Ig (35% cases in the small group of 17 patients), which is in line with previous reports of monoclonal Ig pathogenic involvement in C3G [82,83,99].…”
Section: Acquired Ap Abnormalities In C3gsupporting
confidence: 89%
“…Moreover, studies have shown that iC3b is the main constituent of the dense deposits in the GBM. Both CFI and CFH are essential for C3b cleavage to iC3b, but the abnormalities of CFH, not CFI are responsible for the disease occurrence [9,83,87]. This was demonstrated in an animal model, where CFH-deficient mice, which were also deficient in factor I, did not develop DDD but showed C3 mesangial deposition instead [86].…”
Section: Clinical Features Of C3gn and Dddmentioning
confidence: 98%
See 3 more Smart Citations